Analysis of the Influence of Credit Risk, Liquidity Risk, Interest Rates, and Inflation on Profitability at BPR Bank Bogor City - Bhima Irsi Faliandri Irman; Cecep Taufiqurrahman (Publikasi Indonesia, 2026)
This study aims to analyze the influence of credit risk, liquidity risk, interest rates, and inflation on profitability in BPR Bank Kota Bogor. The dependent variables in this study are profitability proxied by Return on Assets (ROA), while the independent variables include Non-Performing Loan (NPL), Loan to Deposit Ratio (LDR), interest rates, and inflation. The type of research used is quantitative research with an associative approach. The data used was secondary data in the form of financial statements of BPR Bank Bogor City as well as macroeconomic data obtained from official institutions. The research data is in the form of a time series for the period January 2021 to September 2025 which is compiled in the form of monthly data using a trend-based interpolation approach from annual data. The analysis method used is multiple linear regression with the help of statistical software. The results showed that partially the variables of credit risk (NPL), liquidity risk (LDR), interest rate, and inflation did not have a significant effect on profitability (ROA). Simultaneously, the four independent variables also did not have a significant effect on profitability. The value of the determination coefficient shows that the ability of independent variables to explain variations in profitability is relatively low, so there are other factors outside the model that are more dominant in influencing the bank's profitability.